2011
DOI: 10.1038/eye.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroid vs hypothyroid eye disease: the same severity and activity

Abstract: Purpose To compare demographics, severity, and activity of thyroid eye disease (TED) in patients with hyperthyroidism (Hr-TED) vs primary hypothyroidism (Ho-TED). Patients and MethodsIn a cross-sectional study, demographics, complete eye examination, severity score (NOSPECS, total hundred eye score), clinical activity score, and Rundle grading were recorded for patients with TED and different thyroid disorders referred from an endocrinology clinic from 2003 to 2006. Results TED was clinically found in 303 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
4
26
3
Order By: Relevance
“…Upon comparing the other clinical and demographic features of hypo- and hyperthyroid orbitopathy, it was observed that hypothyroid orbitopathy occurred more frequently in females ( P = 0.059) which was in keeping with previous studies. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Upon comparing the other clinical and demographic features of hypo- and hyperthyroid orbitopathy, it was observed that hypothyroid orbitopathy occurred more frequently in females ( P = 0.059) which was in keeping with previous studies. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The activity of TED was similar between patients with either hyper or hypothyroidism in the present study, which paralleled the results of previous research. 21 It has been found that the severity and activity of TED are often dissimilar among different populations. For example, an investigation of 346 patients that classified patients according to EUGOGO reported no TED in 73.7%, mild and inactive TED in 20.2%, and moderate-to-severe and active TED in 5.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, after discarding 25 articles for different reasons (all the patients had hyperthyroidism, did not present ophthalmopathy, or it was not possible to determine the prevalence) 14 articles met all the inclusion criteria, but two articles had the same sample because they were made in the same population. To avoid overrepresentation of this cross-sectional study, we included only the data of one of them [ 22 , 23 ] (Fig. 1 ) (Additional file 3 ).…”
Section: Resultsmentioning
confidence: 99%